2023
DOI: 10.7554/elife.83855
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent flexibility in a molecularly diverse central-to-peripheral auditory feedback system

Abstract: Brainstem olivocochlear neurons (OCNs) modulate the earliest stages of auditory processing through feedback projections to the cochlea and have been shown to influence hearing and protect the ear from sound-induced damage. Here, we used single-nucleus sequencing, anatomical reconstructions, and electrophysiology to characterize murine OCNs during postnatal development, in mature animals, and after sound exposure. We identified markers for known medial (MOC) and lateral (LOC) OCN subtypes, and show that they ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 132 publications
3
31
0
Order By: Relevance
“…The finding that LOCs-but not MOCs-exhibited changes in expression of neural signaling molecules following NE (Figs. 1E, S1D-F), combined with prior findings of long-lasting changes in protein expression of such molecules (5,15,33), suggested a distinct role for LOCs in modulating cochlear properties following NE. To test how LOCs affect auditory function after NE, we developed an intersectional genetic approach to selectively access LOCs bilaterally, without impacting MOCs or other cells in the auditory brainstem.…”
Section: Genetic Strategy For Specifically Targeting Locsmentioning
confidence: 56%
See 3 more Smart Citations
“…The finding that LOCs-but not MOCs-exhibited changes in expression of neural signaling molecules following NE (Figs. 1E, S1D-F), combined with prior findings of long-lasting changes in protein expression of such molecules (5,15,33), suggested a distinct role for LOCs in modulating cochlear properties following NE. To test how LOCs affect auditory function after NE, we developed an intersectional genetic approach to selectively access LOCs bilaterally, without impacting MOCs or other cells in the auditory brainstem.…”
Section: Genetic Strategy For Specifically Targeting Locsmentioning
confidence: 56%
“…However, this binary classification scheme belies a more nuanced reality: as with cellular subtypes identified elsewhere in the brain (65)(66)(67)(68), LOC subtypes appear to exist along a spatially defined continuum, with a gradient of gene expression blending LOC2s into LOC1s along the medial-lateral axis of the LSO (5). We have previously shown that this gradient persists at the protein level after NE, even as the fraction of peptide-expressing LOCs increases (5). Determining the gene-regulatory programs that establish this expression gradient and examining how these programs are altered by LOC activity constitutes a rich avenue for future study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For inhibition, there may be an additional direct projection from the CN 85 , but poly-synaptic inputs are likely because of the ~3-4 ms delay between first and second clusters of IPSCs in most recordings. Potential polysynaptic inhibitory inputs from auditory neurons include the LNTB 86,87 , the superior peri-olivary nucleus (SPON) 88,89 , other inhibitory neurons in the VNTB 90 , or the MOC neurons themselves, which are cholinergic but likely also GABAergic [91][92][93] .…”
Section: Functional Synaptic Inputs To Moc Neuronsmentioning
confidence: 99%